First report of a snout weevil Alcidodes sp. (Coleoptera: Curculionidae) field infestation on mango Mangifera indica L. (Anacardiaceae) in Perlis, Malaysia - Nurul Huda A.,; Che Salmah M.R.,; Hamdan A.,; Abdul Razak M.N., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
An infestation of a snout weevil Alcidodes sp. (Coleoptera: Curculionidae) on Mangifera indica L. (Anacardiaceae) was scientifically reported for the first time in Malaysia. This snout weevil causes severe damage on young stems and flower panicles. Even though the tree survived from a few infestations, but severe cases could pose a serious economic implication on the productivity of the crop. Thus more research regarding the pest management of M. indica is required to maximize mango production in Malaysia.